2023
DOI: 10.1097/md.0000000000033297
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic effect of metastasis patterns on overall survival in organ metastatic lung adenocarcinoma

Abstract: The effect of various metastases patterns on the prognosis of lung adenocarcinoma (AD) remains unknown. The purpose of our retrospective study is to determine whether various metastases patterns have a prognostic impact on patients with organ metastatic lung AD. Patient data was extracted from the Surveillance, Epidemiology, and End Results (SEER) database. The Kaplan–Meier method was chosen for the evaluation of overall survival (OS) rate. Univariable and multivariable Cox regression analyses were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Our research found that the bone is the most common site of organ metastasis in ASC. Similarly, previous articles have shown that bone and brain (25–40%) are the most common sites of metastasis in NSCLC [ 7 , 8 ]. We investigated the impact of metastatic patterns on the survival of ASC.…”
Section: Discussionsupporting
confidence: 56%
“…Our research found that the bone is the most common site of organ metastasis in ASC. Similarly, previous articles have shown that bone and brain (25–40%) are the most common sites of metastasis in NSCLC [ 7 , 8 ]. We investigated the impact of metastatic patterns on the survival of ASC.…”
Section: Discussionsupporting
confidence: 56%
“…Notably, patients with lung metastasis exhibited the longest OS, and multivariate Cox analysis further corroborated these findings, demonstrating that patients with lung metastasis had a more favorable prognosis, which aligns with previous research. [18] However, despite the relatively better prognosis associated with lung metastasis compared to metastasis to other organs, we recommend regular monitoring of suspicious lung nodules to mitigate the risk of death due to the high incidence of lung metastasis. Patients with bone metastasis had the worst OS, and Cetin et al [19] study found that bone metastasis is a significant risk factor that affects the prognosis of LUSC patients, significantly impacting their quality of life, increasing their risk of death, and leading to at least 1 skeletal-related event per year.…”
Section: Discussionmentioning
confidence: 99%